PENGARUH CUSTOMIZATION, BASIC MARKET ORIENTATION DAN COMPETITIVE BENCHMARKING TERHADAP CUSTOMER RETENTION (Studi Empiris pada UMK sambel pecel di Kota Madiun) - Kurniawati, Dyah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The economic crisis that is being experienced by several major countries in the world, including America, is indirectly affecting the economy in Indonesia. The weakening of the rupiah exchange rate against the United States dollar made the national economy worse. The effect is very influential on various sectors until the termination of labor. However, when the national economy became increasingly sluggish, small businesses were able to survive. This sector can be a savior because it is able to create new jobs for the community. The purpose of this study is to analyze the effect of customization, basic market orientation and competitive benchmarking on customer retention. The sample in this study was UMK sambel pecel in Madiun City, with accidental sampling technique. The results of the study found that customization has a significant effect on customer retention, while basic market orientation and competitive benchmarking have no effect on customer retention.